EDUKASI ILMU GEOGRAFI TERAPAN: BIOGEOGRAFI PADA MURID XII IPS SMA IT NUR HIDAYAH: APPLIED GEOGRAPHY SCIENCE EDUCATION: BIOGEOGRAPHY FOR XII IPS STUDENTS OF SMA IT NUR HIDAYAH - Aziz Akbar Mukasyaf (LPPM Universitas Abdurrab, 2024)
Biogeography is a branch of applied geography that studies about distribution of living organisms and their ecosystems in a biological community in a geographic area. Biogeography has an important role because it is connected to biological, agricultural and forestry sciences, such as understanding the evolutionary of organisms from geographic point of view, biodiversity conservation, environmental engineering and its application in the fields of agriculture and forestry. Geography is part of the social sciences. However, the subjects of social science taught in the Indonesian school curriculum are not comprehensive. In fact, the social science subject of geography is integrated with the concepts of social sciences, humanity, natural sciences, and even a combination of various issues. Thus, there is a possibility of a lack of competencies needed for students to advanced their studies. This activity was carried out through a offline seminar at SMA IT Nur Hidayah. The participants were students of class XII IPS total 83 students. As 96% of students were satisfied and responded well to this activity because they obtained new information that was not available during teaching and learning activities in high school in general. A total of 85% percent of students expressed the importance of study material.